Penerapan Jaringan Syaraf Tiruan Metode Backpropagation Dalam Memprediksi Konsentrasi Program Studi Berbasis Web (Studi Kasus: Program Studi Teknik Informatika Universitas Riau) - Chi-chi Salsa Amaza; Feri Candra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Determination of the majoring of the study is very affected in college student’s academic activities. The goal of a major concentration is to help students focus on the major or study that is of based on their potential. University of Riau, Informatics Engineering Study Program has three study concentrations, there are Computing and Vision Intelligence (KCV), Network Based Computing (KBJ), and Software Engineering (RPL). However, choosing a study concentration is not easy for some students. Some students choose the concentrate just to come along with their friends which is not chosen based on their potential. The technology has been used extensively in all aspects of human life, as well as the application of Artificial Neural Networks (ANN). One of the ANN model, backpropagation network is a method of learning that often used in some aspects, one of the aspect is for predicting. Backpropagation is an best method for solving the complex patterns. Therefore, this research will use the backpropagation method on a website basis to predict the majoring of the study programs for college students. This system is designed by using PHP language, HTML dan MySQL database. The obtained accuracy of this system is 95% on the training process and 86% on the testing process with 15 hidden layers combined parameters, 4000 epoch points and and 0.2 learning rate points. Keywords: Artificial Neural Network, Backpropagation, Forecasting, HTML, PHP, Website